Pengelompokan Indikator Kemiskinan di Kabupaten/Kota Aceh Tahun 2021 Menggunakan Analisis Klaster - Naomi Gloria Pasaribu; Famita Wibi Wulandari; Sri Pingit Wulandari (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Poverty in Aceh Province is a significant challenge with variation between districts/cities due to differences in access to education, health, job opportunities, and infrastructure. This study aims to group districts/cities in Aceh based on poverty indicators in 2021 in order to produce a more targeted policy basis. The research data consists of 23 poverty indicators obtained from secondary sources. Cluster analysis is applied using hierarchical (average linkage) and non-hierarchical (K-Means) methods to identify poverty patterns between regions. The results of the hierarchical cluster show that there are two main groups, namely the first cluster has low poverty rates, higher education, strong purchasing power, and low unemployment, while the second cluster has the opposite characteristics. The non-hierarchical analysis (K-Means) produced five clusters with significant differences in poverty levels, labor force participation, education, and economy. These findings provide a basis for the Aceh government to design poverty alleviation policies that focus on the specific needs of each cluster to accelerate the improvement of welfare in all districts/cities in Aceh Province.